The Role of ‘Photobiomodulation (PBM) Therapy’ in Prosthodontics: A Structured Review. - Narendra, Reddi; B. LakshmanaRao, B. LakshmanaRao; Lakshmi, K. Jaya; Yasaswini, K.; Suvarchala, A. Devi; Bhanu, K. Udaya (Journal of Neonatal Surgery, 2025)
Background: Previously referred to as low-level laser treatment (LLLT), photobiomodulation therapy (PBM) uses non-ionizing light sources, usually in the red or near-infrared spectrum, to increase tissue repair and cellular activity. With applications in fixed, removable, implant, and maxillofacial prosthodontics, its function in prosthodontics has expanded beyond postoperative care. Objective: To explore and summarize the current and emerging roles of PBM therapy in various branches of prosthodontics, highlighting its biological benefits, clinical indications, and recent advancements. Methods: A literature review was conducted using databases such as PubMed, Scopus, and Google Scholar. Studies from 2000 to 2024 were included, focusing on PBM applications in prosthodontic disciplines. Keywords included "photobiomodulation", "low-level laser therapy", "prosthodontics", "dental implants", "fixed prostheses", and "maxillofacial prosthetics". Results: PBM has demonstrated clinical advantages in a variety of prosthodontic applications. supports soft tissue recovery around crowns and bridges and lessens post-preparation sensitivity. reduces stomatitis associated with dentures, speeds up mucosal healing, and enhances full and partial denture adaption. improves osseointegration, and boosts early implant stability. enhances tolerance to obturators and face prosthesis, aids in the management of mucositis, and promotes tissue repair after radiation or surgery. Conclusion: PBM is a useful addition to prosthodontics, providing biologically sound and non-invasive advantages that improve patient comfort and treatment results. Its function will probably be further refined by ongoing study and technological advancement, making it a crucial part of contemporary prosthodontic treatment.